Supporting local ownership of transition processes: a key pathway to sustaining the HIV response - Allyala Nandakumar; Damian Walker; Monica Jordan; Lindsay Moore Murphy; Deborah Valerie Stenoien; Eliza Love; Hilary Mwale; Vi Vu; Aishling Thurow; Sarah Konopka (BMJ Global Health)
Globally, an increasing number of countries have made progress towards HIV epidemic control, yet decreasing donor funding and insufficient domestic investments threaten these strides. Within this context, the global community is interested in how to successfully transition responsibility for HIV services from donor-funded programmes to local ownership within the broader healthcare system.This analysis explores how to centre local leadership in transition processes to ensure long-term sustainability of HIV programmes, including moving from external to domestic financing. Existing frameworks show broad consensus on the core elements required to examine readiness and support transition processes; however, many of these frameworks do not address how to ensure that transitions are locally owned. An examination of HIV programmes in Vietnam and Zambia, supported by previous evidence, presented four specific lessons on promoting local ownership and local leadership of transition processes. First, sustainable transitions rely on strong locally led health systems and health system functions. Second, the prioritisation of HIV service and system integration must be locally led to ensure harmonisation with national health sector reforms and priorities. Third, capacity strengthening and consistent engagement with civil society, especially during decision-making processes, can strengthen the sustainability of transition efforts. Finally, decentralising planning and integration processes to regional platforms and actively involving subnational actors is essential in contexts with decentralised health systems. The global community can embrace these lessons to support locally led transitions and improve sustainable HIV services in the long term.